Provisionality and the poem : transition in the work of du Bouchet, Jaccottet and Noël - Wagstaff, Emma (Faux titre ;, 2006)
"As well as examining the imaginative universes of three poets through close attention to the texts, this book considers the important contribution they have made in their prose writing to our understanding of the visual arts and poetry translation, in themselves transitional activities. It argues that these writers have, in different ways, succeeded in crating poetic worlds that attest to close and constantly changing contact with the real."--Jacket